INTEGRASI NILAI MODERASI BERAGAMA DALAM INOVASI DESAIN MEDIA PEMBELAJARAN DIGITAL DI MADRASAH IBTIDAIYAH - Hikam, Fahmul; Fitriyanti, Nur (STIT Al-Ibrohimy Bangkalan, 2025)
Religious moderation is an essential agenda in Islamic education that must be instilled from the primary level, particularly in Madrasah Ibtidaiyah (MI). The values of tawassuth (middle path), tawazun (balance), i’tidal (justice), and tasamuh (tolerance) serve as the foundation for shaping moderate Muslim generations who are tolerant and fair. This study aims to analyze the integration of religious moderation values into the innovative design of digital learning media in MI. The method employed is library research by reviewing primary and secondary literature, analyzed through content analysis. The findings reveal that digital media hold great potential to internalize moderation values through interactivity, visualization, narration, and gamification. Digital comics, interactive animations, reflective modules, and educational games can be designed to suit the characteristics of digital native students. The study contributes theoretically to Islamic education discourse and practically to teachers, students, and policymakers in strengthening digital-based religious moderation.